Correction: An oxygen self-sufficient NIR-responsive nanosystem for enhanced PDT and chemotherapy against hypoxic tumors. Issue 37 (18th September 2020) - Yang, Guoliang; Tian, Jia; Chen, Chao; Jiang, Dawei; Xue, Yudong; Wang, Chaochao; Gao, Yun; Zhang, Weian
Abstract : Correction for 'An oxygen self-sufficient NIR-responsive nanosystem for enhanced PDT and chemotherapy against hypoxic tumors' by Guoliang Yang et al., Chem. Sci., 2019, 10, 5766–5772, DOI: ; 10.1039/C9SC00985J .